Effects of auditory rehabilitation with cochlear implant on tinnitus prevalence and distress, health-related quality of life, subjective hearing and psychological comorbidities: Comparative analysis of patients with asymmetric hearing loss (AHL), double-sided (bilateral) deafness (DSD), and single-sided (unilateral) deafness (SSD) - Olze, Heidi; Ketterer, Manuel Christoph; Péus, Dominik; Häußler, Sophia Marie; Hildebrandt, Lynn; Gräbel, Stefan; Szczepek, Agnieszka J. (Frontiers in Neurology, 2023)
Introduction Auditory rehabilitation with a cochlear implant (CI), in many cases, positively impacts tinnitus. However, it is unclear if the tinnitus-related benefit of CI is equal for patients with various indications for CI. Therefore, this study aimed to determine differences in tinnitus prevalence and distress, health-related quality of life, subjective hearing, perceived stress, and psychological comorbidities between patients diagnosed with asymmetric hearing loss (AHL), single-sided (unilateral) deafness (SSD), and double-sided (bilateral) deafness (DSD) before and six months after cochlear implantation. Methods One hundred-one CI candidates were included in this prospective study (39 AHL patients, 23 DSD patients, and 39 SSD patients). The patients completed questionnaires measuring tinnitus distress, health-related quality of life, subjective hearing, perceived stress, and psychological comorbidities before and 6 months after CI. Results The prevalence of tinnitus in the entire cohort (80.2% before CI) decreased 6 months after CI to 71.3%. The DSD group had the lowest tinnitus prevalence at both time points. The degree of tinnitus-induced distress decreased significantly in all three groups after CI. Differences in quality of life, subjective hearing, and psychological comorbidities between the groups at the study onset disappeared after CI. Significant correlations existed between anxiety, depression, and tinnitus distress in AHL and SSD but not in DSD patients before and after CI. Discussion Our results demonstrate significant differences between the three groups of CI candidates, which might affect the implantation outcome. These differences suggest a need for personalized psychological counseling during the auditory rehabilitation process, focusing on anxiety and depressive symptoms for SSD and AHL patients.